REPRESENTASI NASIONALISME DALAM FILM HABIBIE DAN AINUN (Analisis Semiotika John Fiske dalam film Habibie dan Ainun) - Rony Oktari Hidayat; Arie Prasetio (Universitas Mercu Buana, 2015)
Ainun and Habibie is a film that has the second highest audience after Laskar Pelangi in Indonesia. Film Habibie and Ainun tell the story of Habibie life’s that has a tremendous love for his wife, family and country. Nationalism owned Habibie made him have to choose between his family and his country. Therefore, researchers are interested in analyzing the representation of nationalism owned Habibie and Ainun Habibie film so this research entitled